POTENSI PASAR WISATAWAN CINA: PELUANG DAN TANTANGANNYA - Mertha, I Wayan (Pusat penelitian & Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2007)
Among the world tourist whos visit Bali, the Chinese could be another big potential market segment. Due to this opportunity, this paper tries to find out the characteristics of this market, proposes strategies to gain and analyses the exiting challenges. The conclusion is in the form of recommendation a reminder that Bali has huge, prospective visitors